2012
DOI: 10.1182/blood-2011-04-350413
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 protects against thrombomodulin down-regulation and lung coagulation after particulate matter exposure

Abstract: Exposure to ambient particulate matter (PM) air pollution has been reported to trigger inflammation and thrombosis. However, molecular mechanisms underlying the modulation of coagulation pathways in PM-induced thrombosis remain largely unknown. We report here that Sirt1, a member of class III histone deacetylase, controls lung inflammation and coagulation after PM exposure. Sirt1 knock-out mice exhibited aggravated lung vascular leakage and inflammation after PM exposure, which was correlated with increased NF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 57 publications
3
44
0
1
Order By: Relevance
“…50,51 Our observations are consistent with the protective effects of RSV on the vascular system. [45][46][47][48] Together with RSV, small-molecule activators of SIRT1 have been proposed in the treatment of type 2 diabetes, 52,53 another disease associated with PT. Therefore, polyphenols might become protective molecules against premature aging in PT neonates and associated cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,51 Our observations are consistent with the protective effects of RSV on the vascular system. [45][46][47][48] Together with RSV, small-molecule activators of SIRT1 have been proposed in the treatment of type 2 diabetes, 52,53 another disease associated with PT. Therefore, polyphenols might become protective molecules against premature aging in PT neonates and associated cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…2,44 SIRT1 also regulates the coagulation/inflammation axis 45 and glucose homeostasis. 46 Its downregulation has been associated with diabetes and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The imbalance between levels and activity of MMPs and proteinase inhibitors has been associated with histone deacetylation and defi ciency of sirtuin 1 (SIRT1, a member of class III histone deacetylases). The protective role of SIRT1 was also supported in a study using exposure to ambient PM and gene defi cient mice in which lack of SIRT1 resulted in aggravated lung vascular leakage and infl ammation after PM exposure, which was correlated with increased NF-κB acetylation and activation (Wu et al 2012 ). Pertinent to air pollution induced COPD, increasing expression of SIRT1 was shown to reestablish the balance between proteinases and inhibitors.…”
Section: Proteinases and Extracellular Matrix (Ecm) Interactionsmentioning
confidence: 90%
“…Lastly, experiments using knockout mice demonstrated that Sirt1, a member of class III histone deacetylase, controls lung inflammation and coagulation after PM exposure. PM exposure aggravated lung vascular leakage and inflammation in Sirt1 knockout mice, and these effects were correlated with increased NF-kappaB acetylation and activation [58].…”
Section: Air Pollutants and Histonesmentioning
confidence: 96%